Entrepreneurial management and prospects for sustainability of the hablon industry of Miagao, Iloilo - Hernando, Christine Mae D. (Danyag :the UPV journal of humanities and social sciences)
"This paper presents the entrepreneurial management and sustainability of the hablon industry of Miagao, Iloilo. It examines the business environment of the hablon enterprises, their business operations, and access to business services, among others. It recommends policy initiatives, capability-building programs, and other interventions that could enhance sustainability of the hablon industry."